Relationship Between Social Support and Emotional Regulation to the Resilience of Health Personnel in the COVID-19 Pandemi at Purwosari Health Centre in Pasuruan Regency - Hasnayanti, Afiyah; Puspitasari, Dwi Nikmah (Jurnal Sains Psikologi, 2023)
This study aims to determine the relationship between social support and emotional regulation on the resilience of health workers who work during the Covid-19 pandemic at the Purwosari Health Center, Pasuruan Regency. The measuring tool used in this study was a questionnaire consisting of three adaptation scales. The Multidimensional Scale of Perceived Social Support, consisting of 12 items, was used to measure social support variables, while the Difficulty in Emotion Regulation Scale-16 was used to measure emotion regulation variables, and The Connor-Davidson Resilience Scale, consisting of 25 items, was used to measure resilience variables. The data that has been collected is then analyzed using simple linear and multiple linear correlations. The study results show a significant relationship between social support and emotional regulation on the resilience of health workers working during the Covid-19 pandemic.